The trumpeter of Krakow - Kelly, Eric P. (Eric Philbrook), 1884-1960. (New York, Macmillan, 1966)
A Polish family in the Middle Ages guards a great secret treasure and a boy's memory of an earlier trumpeter of Krakow makes it possible for him to save his father.
Keywords: Newbery Medal; Middle Ages -- Fiction; Poland -- History -- Casimir IV, 1447-1492 -- Juvenile fiction; Poland -- History -- Casimir IV, 1447-1492 -- Fiction